Population Fluctuation and Abundance of Fruit Flies, Bactrocera (Diptera: Tephritidae) in Mango Orchards - Salmah, Mohamed; Nur Azura, Adam; Rita, Muhammad; Wei Hong, Lau; Marina, Roseli; Hamdan, Ahmad (2015)
Bactrocera is the most problematic tephritid fruit flies and agricultural important pests due to the severe damages caused to commercial fruits such as mango (Mangifera indica L.). In order to determine the population fluctuation and abundance of Bactrocera species in mango orchards, a survey was carried out in four mango orchards located in Jitra, Kedah; Kepala Batas, Penang; Bukit Changgang, Selangor and Pulau Gadong, Melaka. Adult of fruit flies were trapped using methyl-euganol (ME) attractant traps from February to June 2014. The trapped fruit flies were collected bimonthly and placed in 70% ethanol for preservation and brought to the laboratory for sorting process and species identification. Daily meteorological data (i.e.temperature, relative humidity and rainfall) were recorded during the sampling period. A total of 33467 fruit flies were trapped in all locations with three Bactrocera species were identified known as B. papayae, B. carambolae, and B. umbrosa. Among them, B. papayae was recorded the highest numbers (92.7%) compared to B. carambolae (7.0%) and B. umbrosa (0.3%). This indicated that B. papayae is predominance species in mango orchards. The abundance of fruit flies obtained was significantly different (P<0.05) among the mango orchards. Nevertheless, there was no significant difference (P>0.05) between the abundance of fruit flies in Pulau Gadong and Kepala Batas as well as between Bukit Changgang and Pulau Gadong. Overall, the population fluctuation of Bactrocera species between weeks showed no significant difference (P>0.05). However, the population of fruit flies start to increase when the mango plants reached the fruiting stage. The highest number of fruit flies captured was recorded at matured and ripe mango stage in all locations. The temperature showed no significant association (P>0.05) with the fruit flies population in all locations. Relative humidity in Pulau Gadong and Bukit Changgang and rainfall in Pulau Gadong also showed no significant correlation (P>0.05). However, fruit flies population was positively correlated (P<0.05) with relative humidity in Kepala Batas and Jitra, and rainfall in Bukit Changgang, Kepala Batas and Jitra.